Iron in Chronic Brain Disorders: Imaging and Neurotherapeutic Implications - Stankiewicz, James; Panter, S. Scott; Neema, Mohit; Arora, Ashish; Batt, Courtney E.; Bakshi, Rohit (Neurotherapeutics, 2007)
Iron is important for brain oxygen transport, electron transfer, neurotransmitter synthesis, and myelin production. Though iron deposition has been observed in the brain with normal aging, increased iron has also been shown in many chronic neurological disorders including Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis. In vitro studies have demonstrated that excessive iron can lead to free radical production, which can promote neurotoxicity. However, the link between observed iron deposition and pathological processes underlying various diseases of the brain is not well understood. It is not known whether excessive in vivo iron directly contributes to tissue damage or is solely an epiphenomenon. In this article, we focus on the imaging of brain iron and the underlying physiology and metabolism relating to iron deposition. We conclude with a discussion of the potential implications of iron-related toxicity to neurotherapeutic development.